2021
DOI: 10.2499/p15738coll2.134374
|View full text |Cite
|
Sign up to set email alerts
|

Immediate impacts of COVID-19 on the aquaculture value chain in Ghana

Abstract: Ghana's aquaculture sector is among the recent success stories of fast-growing agricultural value chains in Africa south of the Sahara. The sector has also shown its vulnerability, with the infectious spleen and kidney necrosis virus spreading through tilapia farms in Lake Volta in late 2018. The global COVID-19 human pandemic reached Ghana in early 2020, affecting the sector directly and indirectly. Using a value chain approach, phone interviews were conducted with 369 small-scale fish farmers in six major pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…At the individual or community level, people strived to string together their different mechanisms to cope with the situation. A study in Myanmar showed that people resorted to borrowing from friends or selling their household assets such as gold, land, or jewellery (Ragasa et al, 2021). However, these alternatives typically were not sufficient to prevent increased food insecurity for extended periods.…”
Section: Policy Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the individual or community level, people strived to string together their different mechanisms to cope with the situation. A study in Myanmar showed that people resorted to borrowing from friends or selling their household assets such as gold, land, or jewellery (Ragasa et al, 2021). However, these alternatives typically were not sufficient to prevent increased food insecurity for extended periods.…”
Section: Policy Discussionmentioning
confidence: 99%
“…A survey in Myanmar between January and June 2020 (n =1,072) showed that 51% of respondents lost jobs in various livelihood activities. People without land were mostly affected more by the crisis, mainly because of loss in farm incomes and the absence of non-farm employment (Ragasa et al, 2021). The authors also found that women and men in these landless households were equally affected by lower wages and lack of farm work during COVID-19.…”
Section: Covid-19 Impact On Consumersmentioning
confidence: 96%
See 2 more Smart Citations
“…In the wake of the COVID‐19 crisis, other climatic calamities have affected ecosystems and livelihoods, especially those of fishers who depend on fishing as their sole source of income in Kenya (Aura et al., 2020 ) and also on a global scale (Sarà et al., 2022 ). In Ghana, the crisis has reduced incomes for most actors along the aquaculture value chain and is anticipated to reduce future production as there are disruptions in input and output markets (Ragasa et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%